2007
DOI: 10.1074/jbc.m610127200
|View full text |Cite
|
Sign up to set email alerts
|

The Cytoplasmic Domain of Transferrin Receptor 2 Dictates Its Stability and Response to Holo-transferrin in Hep3B Cells

Abstract: Transferrin receptor 2 (TfR2) is a homolog of transferrin receptor 1 (TfR1), the receptor responsible for the uptake of iron-loaded transferrin (holo-Tf) into cells. Unlike the ubiquitous TfR1, TfR2 is predominantly expressed in the liver. Mutations in TfR2 gene cause a rare autosomal recessive form of the iron overload disease, hereditary hemochromatosis. Previous studies demonstrated that holo-Tf increases TfR2 levels by stabilizing TfR2 at the protein level. In this study we constructed two chimeras, one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 40 publications
2
32
0
1
Order By: Relevance
“…Two studies have shown that the TfR2 protein is stabilized by diferric transferrin (17,28). The cytoplasmic domain of TfR2 appears to be responsible for this stabilization, because a chimeric receptor containing the cytoplasmic domain of TfR2 fused to the transmembrane and ectodomain of TfR1 retained the ability to be stabilized by diferric transferrin (4). Other experiments have shown that diferric transferrin increases the fraction of TfR2 being targeted to the recycling pathway and decreases the amount being targeted to the late endosomes and lysosomes for degradation (16).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have shown that the TfR2 protein is stabilized by diferric transferrin (17,28). The cytoplasmic domain of TfR2 appears to be responsible for this stabilization, because a chimeric receptor containing the cytoplasmic domain of TfR2 fused to the transmembrane and ectodomain of TfR1 retained the ability to be stabilized by diferric transferrin (4). Other experiments have shown that diferric transferrin increases the fraction of TfR2 being targeted to the recycling pathway and decreases the amount being targeted to the late endosomes and lysosomes for degradation (16).…”
Section: Discussionmentioning
confidence: 99%
“…Down-regulation of GRAIL did not abolish the increase in stability of TfR2 in the presence of Tf. 3 Previous studies indicate that Tf increases the recycling of TfR2 from endosomal compartments back to the plasma membrane (21,23,32). These results suggest that recycling occurs from an earlier compartment than the CD81/GRAIL-mediated degradation signal occurs.…”
Section: Figure 4 Knockdown Of Cd81 Stabilizes Tfr2 By Increasing Itmentioning
confidence: 92%
“…The pcDNA3-TfR2⌬CD encoding TfR2 lacking its cytoplasmic domain was generated from pcDNA3-TfR2 by PCR. The chimera, TfR2CD/TfR1-f, containing the cytoplasmic domain of TfR2 and the transmembrane and ecto-domains of TfR1 followed by a Flag epitope was described previously (21). GRAIL cDNA was amplified from the RNA isolated from Hep3B cells, cloned into the pcDNA3 vector, and verified by sequencing.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations